RENCANA PEMBANGUNAN SUPER MARKET LION SUPER INDO - Basuki, Agus Tri (Jurnal Ekonomi & Studi Pembangunan, 2010)
This study aimed to see whether the development plans of the Lion Super IndoSuper Market meet the economic feasibility. Investment plans of the establishment of the Super Indo Supermarket at Jalan Parangtritis is one of the business development program of PT Lion Super Indo through the opening of branch offices. Based on the results of feasibility studies, investment plans are feasible to implement, especially in terms of some aspects of the feasibility. Although it is economically feasible, but Lion Super Indo need to do a Corporate Social Responsibility which is expected to reduce the negative externalities.